2019
DOI: 10.1530/joe-18-0391
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone and ovarian aging in mares

Abstract: Anti-Müllerian hormone (AMH) is used as a marker of follicle population numbers and potential fertility in several species including horses but limited data exist across the lifespan. No one has decreased ovarian reserve experimentally to investigate whether a corresponding, quantitative decrease in AMH results. Concentrations of AMH across the lifespan were compiled from 1101 equine females sampled from birth to >33 years of age. Young and old mares (averaging 6 and 19 years) were hemi-ovariectomized and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 71 publications
8
28
1
5
Order By: Relevance
“…Furthermore, others reported that AMH concentrations begin to decline in mares only after 20 years of age. 43 In contrast, in our study older mares didn't have significantly lower AMH and AFC measurements compared to other age groups, but the AFC was higher in mid-dle-aged mares than in young mares. This could be explained by the relatively unequal distribution of mares between the different age groups in our study, but also by the previously reported large individual differences in follicular populations between individuals of the same age.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…Furthermore, others reported that AMH concentrations begin to decline in mares only after 20 years of age. 43 In contrast, in our study older mares didn't have significantly lower AMH and AFC measurements compared to other age groups, but the AFC was higher in mid-dle-aged mares than in young mares. This could be explained by the relatively unequal distribution of mares between the different age groups in our study, but also by the previously reported large individual differences in follicular populations between individuals of the same age.…”
Section: Discussioncontrasting
confidence: 97%
“…Associations between these two biomarkers and age have been demonstrated in mares, cows and women, and are likely to reflect the follicular origin of AMH and the diminishing ovarian reserve. 8,15,18,21,43,44 Similarly to our findings, Claes et al (2015) 18 observed a strong or moderate relationship between AFC and AMH concentrations in older resp. middle-aged mares, but, in contrast to our study, didn't find a correlation in young mares.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations